Robo2 Drives Target-Selective Peripheral Nerve Regeneration in Response to Glia-Derived Signals - Murphy, Patricia L.; Isaacman-Beck, Jesse; Granato, Michael (The Journal of neuroscience, 2022)
Peripheral nerves are divided into multiple branches leading to divergent synaptic targets. This poses a remarkable challenge for regenerating axons as they select their original trajectory at nerve branch-points. Despite implications for functional regeneration, the molecular mechanisms underlying target selectivity are not well characterized. Danio Rerio (zebrafish) motor nerves are composed of a ventral and a dorsal branch that diverge at a choice-point, and we have previously shown that regenerating axons faithfully select their original branch and targets. Here we identify robo2 as a key regulator of target-selective regeneration (sex of experimental subjects unknown). We demonstrate that robo2 function in regenerating axons is required and sufficient to drive target-selective regeneration, and that robo2 acts in response to glia located precisely where regenerating axons select the branch-specific trajectory to prevent and correct axonal errors. Combined, our results reveal a glia-derived mechanism that acts locally via axonal robo2 to promote target-selective regeneration. SIGNIFICANCE STATEMENT Despite its relevance for functional recovery, the molecular mechanisms that direct regenerating peripheral nerve axons toward their original targets are not well defined. Zebrafish spinal motor nerves are composed of a dorsal and a ventral branch that diverge at a stereotyped nerve branch-point, providing a unique opportunity to decipher the molecular mechanisms critical for target-selective regeneration. Using a combination of live cell imaging and molecular-genetic manipulations, we demonstrate that the robo2 guidance receptor is necessary and sufficient to promote target-selective regeneration. Moreover, we demonstrate that robo2 is part of a genetic pathway that generates transient, spatially restricted, and tightly coordinated signaling events that direct axons of the dorsal nerve branch toward their original, pre-injury targets.